Evaluasi Kadar Antosianin Beras Merah dan Hitam Serta Formulasi Sediaan Masker Peel-Off - Yogaswara, I Gusti; Wirasisya, Dyke Gita; Juliantoni, Yohanes; Hidayat, Lalu Husnul (LPPM Universitas Mataram, 2024)
Brown rice and black rice have high levels of anthocyanins so they have the potential to be developed as peel-off masks. This study aims to determine the anthocyanin levels of brown rice and black rice ethanol extracts and carry out formulations and evaluations of the physical properties of the peel-off mask formula with the highest anthocyanin levels. The anthocyanin levels of the two samples were determined using the pH difference method. Black rice samples produced the highest anthocyanin levels. Peel-off mask preparations are formulated from samples with the highest anthocyanin levels. Evaluation of the preparation includes organoleptic testing, homogeneity, dispersal power, pH and the time the preparation dries. Anthocyanin levels of black and red rice were 123.2±6,312 and 24.9±4,117 mg/100 gr, respectively. The maske r peel-off preparation was successfully formulated from black rice with a content of 1%. The evaluation results showed that the peel-off mask was purple, gel shape, distinctively scented, homogeneous, spreading power was 6.0 cm, pH 5.0 and the preparation time dried 20.33 ± 0.15 minutes. Based on research, it can be concluded that the formula of the peel-off mask of 1% black rice ethanol extract has met the physical requirements of the preparation.